Neuromanagement Under the Light of Maqasid Sharia - Yosita Nur Wirdayanti; Muhammad Abdul Ghoni (Universitas Darussalam Gontor, 2019)
Technology advancement and Industrial revolution 4.0 engagement are increasingly seen as powerful tool for making innovation, managerial efficiency of the company. New brain imaging technologies have motivated neuromanagement studies of the internal order of the mind and its links with the spectrum of human decisions from harmful and injustice decision. The main achievement of this study is to explain how neuromanagement works under light of Maqasid al Shariah. As spirit of Shariah is based on wisdom and achieving people’s welfare in this life and the afterlife. Shariah is all about justice, wisdom, and good. This paper contributes to the literature by explaining neuromanagement and Maqasid al Shariah. In fact, that there is a lack of literature related to neuromanagement and Maqasid al Shariah. This research will, therefore, provide to the neuromanagement decision making in accordance with the Maqasid al Shariah.